2018
DOI: 10.4047/jap.2018.10.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Repair bond strength of resin composite to bilayer dental ceramics

Abstract: PURPOSEThe purpose of this study was to investigate the effect of various surface treatments (ST) on the shear bond strength of resin composite to three bilayer dental ceramics made by CAD/CAM and two veneering ceramics.MATERIALS AND METHODSThree different bilayer dental ceramics and two different veneering ceramics were used (Group A: IPS e.max CAD+IPS e.max Ceram; Group B: IPS e.max ZirCAD+IPS e.max Ceram, Group C: Vita Suprinity+Vita VM11; Group D: IPS e.max Ceram; Group E: Vita VM11). All groups were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Thus, grinding was selected as the base treatment and included in all groups. For grinding procedure, SiC paper was selected to replace a carbide or fine diamond bur 24. It has the advantage that it can give more uniform and stable force and is easy to apply than carbide or diamond bur in laboratory research.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, grinding was selected as the base treatment and included in all groups. For grinding procedure, SiC paper was selected to replace a carbide or fine diamond bur 24. It has the advantage that it can give more uniform and stable force and is easy to apply than carbide or diamond bur in laboratory research.…”
Section: Discussionmentioning
confidence: 99%
“…Another system to create surface microirregularities is sandblasting LS 2 with aluminum oxide particles. Nevertheless, it has been shown that this procedure, as well as laser etching, can determine excessive loss of material, with surface modifications that are less uniformly distributed than after HF etching and that can significantly reduce flexural strength [42,43]. In addition to micromechanical interlocking, as for all silicabased materials, adhesive bonding of LS 2 is efficiently increased by silane, ensuring a chemical interaction between the resin-based agent and the ceramics, obtained forming strong siloxane linkages [44][45][46][47][48][49][50].…”
Section: Surface Treatment and Cementationmentioning
confidence: 99%
“…11 Several prior studies have been conducted to compare the efficiency of the protocol using 2step surface treatments and silane followed by concentration and application times. [12][13][14] Comparative outcomes are provided by these studies on field-emission scanning electron microscopic analysis, micromorphological analysis, tensile bond strength, shear bond strength, and contact angle.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%